Heterologous expression of maize-derived antimicrobial peptide ZmES4 in Escherichia coli for potential plant pathogen control - Amien, Suseno; Nurdiana, Dadi; Istifadah, Noor; Wicaksana, Noladhi; Salsabila, Haifanisa (Universitas Padjadjaran, 2025)
ZmES4 is a plant-derived antimicrobial peptide (AMP) from maize that shows promise as a biocontrol agent against plant pathogenic organisms. In the context of growing challenges in sustainable agriculture, AMPs like ZmES4 represent innovative alternatives to chemical pesticides. This study focuses on the structural characterization and heterologous expression of the ZmES4 peptide in Escherichia coli (E. coli). The gene encoding ZmES4 was obtained from the maize female gametophyte (NCBI Reference Sequence: NM_001112150.3) and cloned into the pET24d(+) expression vector using NcoI and XhoI restriction sites. Transformation into E. coli BL21 (DE3) cells enabled recombinant expression upon induction with isopropyl β-D-1-thiogalactopyranoside (IPTG). Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and Bradford assays confirmed the expression of ORF-ZmES4, with protein concentrations ranging from 14.647 to 63.606 mg/mL. The successful expression of ZmES4 in E. coli highlights its potential application as a recombinant AMP for future plant disease management strategies.